Phenotypic characterization for milk traits in crossbred cattle population from the state of Norte de Santander - Guerrero, Luisa Fernanda Naranjo (2023)
Crossbred cattle are used in dual-purpose systems to obtain meat and milk, becoming one of Colombia's systems with the greatest presence. However, studies characterizing productive variables in crossbred individuals are scarce, making it pertinent to conduct analyses evaluating their potential. The objective of this study was to phenotypically characterize a population of crossbred cattle from the state of Norte de Santander (Colombia) in terms of milk traits. Up to a maximum of 4 controls per female was obtained, and information on milk yield (MY), fat percentage (FP), protein percentage (PP), and somatic cell count (SCC) of first parity crossbred females was evaluated. The information was filtered and analyzed with the R program. The mean, standard deviation, and general variation coefficient were calculated for each trait and the means and deviations by non-genetic categorical factors. For the numeric factors, graphs of trends related to the response variables were made. Multiple correspondence analysis was performed, and the standardized residual values were estimated to recognize associations between levels of non-genetic factors and each trait. Mean values for controls were: 3.06±1.40 kg/day (MY), 3.21±0.40% (PP), 3.32±0.77% (FP), and 357±256x103 cells/ml (SCC). The non-genetic factors that showed the most significance were the pasture type, the control season, and the region. Thus, MY from 1.00 to 2.00 kg is associated with the levels of region 1 (R1) and summer 1 (S1), MY from 2.10 to 3.99 kg with region 2 (R2), group 1 (G1) and winter 1 (W1), MY from 4.00 to 8.30 kg with R1, group 3 (G3) and W1, PP from 2.45 to 2.99% there was association with G1, PP from 3.00 to 3.40% with group 2 (G2), PP from 3.41 to 6.04% with G3, FP of 1.94 to 3.00% is associated with R1, G3, S1, and S2, FP of 3.01 to 4.00% with R2, G1 and W1, FP from 4 to 4.82 % with region 3 (R3), G2, and S1, SCC from 8.00 to 100x103 cells/ml is associated with R1, R3, and S1, SCC of 101 to 499x103 cells/ml with R2, G1, and W1. Finally, SCC of 500 to 888x103 cells/ml is associated with R2 and W1. A variation of medium to high magnitude of the traits evaluated within the population was evidenced, revealing that no standards that allow unifying the management of animals within herds, which can affect the efficiency of dual-purpose systems.